'Rehabilitation aids for the blind': disability and technological knowledge in Canada, 1947-1985. (2nd January 2020) - Robertson, Beth A.
ABSTRACT: Contrary to stereotypes that portray people with disabilities as passive recipients of technological innovation, individuals with sensory and mobility impairments have played key roles in the invention, design and use of adaptive or assistive devices over the course of the twentieth century. This article interrogates this history through a case study focusing on the research program of James Swail, an engineer with the National Research Council (NRC) of Canada from 1947 until 1985. As someone who was himself blind, Swail's predicated his design work on an asset-based understanding of disability. He strived to disrupt conceptions of both the technological functionality and economic rationality of technologies produced for and by disabled people in mid-twentieth century Canada. Framed within a medical model, however, the overall fate of these machines mirrored back the imagined inability of people with disabilities to become fully participating members of the society in which they lived.